Long-term cultivation alter soil bacterial community in a forest-grassland transition zone - Bai, Zhenyin; Zheng, Lingbo; Bai, Zhenjian; Jia, Aomei; Wang, Mingjun (Frontiers in Microbiology, 2022)
Changes in land use types can significantly affect soil porperties and microbial community composition in many areas. However, the underlying mechanism of shift in bacterial communities link to soil properties is still unclear. In this study, Illumina high-throughput sequencing was used to analyze the changes of soil bacterial communities in different land use types in a forest-grassland transition zone, North China. There are two different land use types: grassland (G) and cultivated land (CL). Meanwhile, cultivated land includes cultivated of 10 years (CL10) or 20 years (CL20). Compared with grassland, cultivation decreased soil pH, SOC and TN, and significantly increased soil EC, TP, TK, AN, AP and AK, and soil properties varied significantly with different cultivation years. Long-term culture increases the diversity of bacterial communities. The relative abundance of Proteobacteria and Bacteroidea increased, while that of Actinobacteria and Chloroflexi decreased. Mantel test and RDA analysis showed that TP, AP, SOC and EC were the main factors affecting the diversity of composition of bacterial communities. In conclusion, soil properties and bacterial communities were significantly altered after long-term cultivation. This study provides data support for land use and grassland ecological protection in this region.